COVID-19 in obstetric anesthesia Prospective surveillance of peripartum infections with SARS-CoV-2 and peripartum course of disease in affected women - Sitter, Magdalena; Schlesinger, Tobias; Reinhold, Ann-Kristin; Scholler, Axel; Von Heymann, Christian; Welfle, Sabine; Bartmann, Catharina; Woeckel, Achim; Kleinschmidt, Stefan; Schneider, Sven; Gottschalk, Andre; Greve, Susanne; et al. (Anaesthesist, 2021)
Background In the current pandemic regarding the infection with the SARS-CoV-2-virus and COVID-19 as the disease, concerns about pregnant women, effects on childbirth and the health of the newborn remain high. Initially, due to the early manifestation of the disease in younger patients, high numbers of COVID-19 patients in women needing peripartum care were expected. Objective This article aims to provide a general overview over the beginning of the pandemic as well as the second wave of infections in Germany and Switzerland, regarding SARS-CoV-2 positive pregnant women hospitalized for childbirth. We therefore launched a registry to gain timely information over the dynamic situation during the SARS-CoV-2 pandemic in Germany. Material and methods As part of the COVID-19-related Obstetric Anesthesia Longitudinal Assessment (COALA) registry, centers reported weekly birth rates, numbers of suspected SARS-CoV-2 cases, as well as the numbers of confirmed cases between 16 March and 3 May 2020. Data acquisition was continued from 18 October 2020 till 28 February 2021. The data were analyzed regarding distribution of SARS-CoV-2 positive pregnant women hospitalized for childbirth between centers, calendar weeks and birth rates as well as maternal characteristics, course of disease and outcomes of SARS-CoV-2 positive pregnant women. Results A total of 9 German centers reported 2270 deliveries over 7 weeks during the first wave of infections including 3 SARS-CoV-2 positive cases and 9 suspected cases. During the second survey period, 6 centers from Germany and Switzerland reported 41 positive cases out of 4897 deliveries. One woman presented with a severe and ultimately fatal course of the disease, while another one needed prolonged ECMO treatment. Of the women 28 presented with asymptomatic infections and 6 neonates were admitted to a neonatal intensive care unit for further treatment. There was one case of neonatal SARS-CoV-2 infection. Conclusion The number of pregnant women infected with SARS-CoV-2 was at a very low level at the time of delivery, with only sporadic suspected or confirmed cases. Due to the lack of comprehensive testing in the first survey period, however, a certain number of asymptomatic cases are to be assumed. Of the cases 68% presented as asymptomatic or as mild courses of disease but the data showed that even in young healthy patients without the presence of typical risk factors, serious progression can occur. These outcomes should raise awareness for anesthesiologists, obstetricians, pediatricians and intensive care physicians to identify severe cases of COVID-19 in pregnant women during childbirth and to take the necessary precautions to ensure the best treatment of mother and neonate. The prospective acquisition of data allowed a timely assessment of the highly dynamic situation and gain knowledge regarding this vulnerable group of patients.
CRIS-Team WoS Importer:2021-12-03